FTIR-based fingerprinting and discriminant analysis of Apium graveolens from different locations - Kartini Kartini, Lis Arifa Dwi Putri, Mochammad Arbi Hadiyat (Journal of Applied Pharmaceutical Science, 2020)
Apium graveolens (celery) has been utilized as vegetable and medicinal herbs worldwide for centuries, and it especially thrives in the tropical and subtropical regions of Asia and Africa. This herb contains various phytoconstituents, such as limonene, selinene, apigenin, luteolin, and kaempferol, which vary in concentration depending on the type of soil and climate where it grows. This study was conducted to analyze and classify A. graveolens according to their geographical origin by Fourier-transform infrared (FTIR)-based fingerprinting combined with chemometrics: principal component analysis (PCA), cluster analysis (CA), and discriminant analysis (DA). PCA and CA classified 10 samples of A. graveolens into two groups, while DA could determine the group to which the three commercially available A. graveolens belong. In conclusion, FTIR-based fingerprinting, coupled with chemometrics, could discriminate between the A. graveolens crude drugs originated in various locations. As for the group of new samples, it can be predicted by the combination of FTIR-based fingerprinting and DA. The development of analytical methods for geographical provenance of A. graveolens will positively impact the quality control of herbal materials and ultimately guarantee the safety and efficacy of the product.
Keywords: Apium graveolens, FTIR-based fingerprinting, chemometrics, discriminant analysis, geographical origin.